PENGARUH FAKTOR INTERN DAN FAKTOR EKSTERN TERHADAP PRESTASI BELAJAR EKONOMI - Marimin, -; Vemilia, Citra Ayu (Dinamika Pendidikan, 2009)
StudentsÃ¢â¬â¢ achievement is one of success indicator in learning process. One of parameters used to measure succes level is minimal limit over learning target. But, there were a lot of 11th grade social class students in SMA N 1 Pegandon had low score below the minimal limit over learning target. The statements of problems are to know the condition of external and internal factors, to know the influence of external and internal factors toward learning achievement. The number of population was 126 students. The variables were internal factor, external factor and student learning achievement. Data was taken by using observation method, documentation and multiple regressions. The result study showed that internal factors was in good level (54.8%), external factor was in good level (80.16%). It can be concluded that internal factor and external factor gave influences toward student achievement. Thus; it is suggested that students should adapt in daily life with assessement exercise to improve studentsÃ¢â¬â¢ understanding toward subject material. Key words: Internal Factor, External Factor, studentsÃ¢â¬â¢ achievement.